2021
DOI: 10.7150/jca.52187
|View full text |Cite
|
Sign up to set email alerts
|

Centromere Protein F (CENPF) Serves as a Potential Prognostic Biomarker and Target for Human Hepatocellular Carcinoma

Abstract: Overexpression of Centromere Protein F ( CENPF ) is associated with tumorigenesis of many human malignant tumors. But the molecular mechanism and prognostic value of CENPF in patients with hepatocellular carcinoma (HCC) are still unclear. In this essay, expression of CENPF in HCC tumors were evaluated in a series of databases, including GEO, TCGA, Oncomine, GEPIA, The Human Protein Atlas and Kaplan-Meier plotter. It was apparent that mRNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…Huang Y et al . asserted that up-regulation of CENPF was a hazard factor for the prognosis of HCC [ 21 ]. A recent study suggested that overexpressed CENPF exerted as a cancer-driver gene in the formation and development of human cancers [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang Y et al . asserted that up-regulation of CENPF was a hazard factor for the prognosis of HCC [ 21 ]. A recent study suggested that overexpressed CENPF exerted as a cancer-driver gene in the formation and development of human cancers [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression peak of CENPF is in the cell cycle of the G2/M phase. The aberrant expression of CENPF has been found in multiple malignancies, including hepatocellular carcinoma (HCC) [ 19 21 ], prostate cancer [ 22 ], and other carcinomas [ 23 , 24 ], but little literature about ACC. Specifically, the latest studies have acclaimed that overexpression of CENPF markedly promoted cell proliferation in HCC [ 20 ] and induced tumor metastasis in prostate cancer with a poor prognosis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…TOP2A has been reported to be up-regulated in HCC and could be used as a biological indicator to predict HCC prognosis [ 24 ]. CENPF associates with the centromere–kinetochore complex and influences cell proliferation and metastasis in HCC [ 25 ]. In addition, GSVA results showed that proliferation biological pathways, such as mitosis, G 2 /M checkpoint, and E2F targets, were enriched in hepatocytes C4.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of FLVCR1 was significantly associated with poor prognostic value in HCC patients [ 34 ]. CENPF was identified as a potential prognostic biomarker and target for HCC [ 35 ]. It is reported that upregulated RECQL4 [ 36 ], SPC24 [ 37 ], and KIF20A [ 38 ] could predict poor prognosis in HCC, whereas upregulated ZWINT was associated with great prognosis in patients with HCC after surgery [ 39 ].…”
Section: Discussionmentioning
confidence: 99%